Generating a beneficial creative chaos to manage compartmentalization in psychology: A trans-disciplinary approach to intertwine plurality and unity - Bosio, A. Claudio (Rivista di Psicologia Clinica - Open Access, 2023)
The search for a composition between plurality and unity of psychology is developed here by articulating a reflection on three points concerning: the origins of the phenomenon of compartmentalization that can be traced back to a dual configuration - plural and fragmented - of psychology; characteristics that are connected but not coincidental; the acceptability of a trans-disciplinary approach to design a composition of psychology that respects its plural articulation; the choice of the area of health as the elective phenomenical field to test the possibility of composing the plurality and unity of psychology starting from a trans-disciplinary approach.